Magnetic resonance enterographic predictors of one-year outcome in ileal and ileocolonic Crohn’s disease treated with anti-tumor necrosis factor antibodies - Eder, Piotr (Sci Rep, 2015)
The aim of the study was to assess the role of magnetic resonance enterography (MRE) in predicting one-year efficacy of anti-tumor necrosis factor antibodies - infliximab (IFX), adalimumab (ADA) in Crohn’s disease (CD) patients primarily responding to therapy. We performed retrospective analysis among 61 CD patients who had undergone a successful IFX/ADA induction therapy and were treated with maintenance doses. All patients underwent MRE at week 0. We assessed which MRE features were predictive for steroid-free remission at week 52, and which were associated with a secondary loss of response. 44 patients were in steroid-free remission at week 52, 17 - were secondary non-responders. The ROC curve showed that bowel thickening with contrast enhancement analyzed together at week 0 were associated with steroid-free remission at week 52 (p = 0.01; AUC 0.67). Bowel stenosis with or without prestenotic dilatation [OR 5.8 (95% CI 1.4 – 25) and 2.4 (95% CI 1.2 – 5) respectively; p = 0.01] and the presence of intra-abdominal fistulas [OR 1.4 (95% CI 1.1 – 2); p = 0.004] were related to secondary non-response. A high baseline inflammatory activity detected by MRE predicts one-year response in CD after IFX/ADA. In case of bowel stenosis, intra-abdominal fistulas, other therapeutic options should be considered.